When the public good conflicts with an apparent preference for unsustainable behaviour - Collier, Marcus (My University, 2011)
The example of peatlands is used to demonstrate the challenges facing the sustainable management of natural resources in situations where the fragility of an environment is not appreciated by all stakeholders. We reveal, through the use of a survey applying both contingent valuation and discrete choice experiments, that many local people and others within the wider population, value peatlands as an example of a cultural landscape. However, there is a reluctance to stop extracting peat for domestic fuel even though the activity is undermining the ecological sustainability of this same landscape. This resistance is shown to arise because the cutting of peat is a well-established land use and a cessation of peat cutting is perceived to require the abandonment of traditional rights. In addition, the activity is widely regarded as more benign than industrial scale cutting for energy. The value attached to the landscape is an opportunity for conservation policy, but for this to succeed there must be an acknowledgement of local interests.
Keywords: Peatland; Contingent valuation; Choice experiment; Cultural landscape; Property rights; Smart & Sustainable Planet; Environmental Economics; SOCIAL-ECOLOGICAL SYSTEMS; resilience; socio-cultural ecosystem services